DISCOVERING AND PROFICIENCING THE ENGLISH PRONUNCIATION ERRORS - Manurung, Lastri Wahyuni; Saragi, Christina Natalina; Sitinjak, Apriani Silviani (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
By using the results from the ELSA Speak application, the pronunciation skills of second-year English majors at Universitas HKBP Nommensen Medan were examined. The ELSA Speak Application was utilized to determine the kinds of pronunciation faults made by second-year students at the English Department of FKIP Universitas HKBP Nommensen Medan. This study used a descriptive qualitative research design. The ELSA Speak Application and documentation were used to collect data from students' pronunciation diagnoses. Twenty students were selected as the sample, with the population of the study consisting of the students in the English Department at FKIP Universitas HKBP Nommensen Medan. The following are the conclusions: The majority of the sample found that they would